A new Casearia (Salicaceae) from the Atlantic Forest of Brazil - Nepomuceno, Francisco Álvaro Almeida; Alves, Marccus (Phytotaxa, 2017)
A new species of Casearia is described from Coastal Lowland Forest and Sub-montane Forest in the states of Paraíba and Pernambuco. The new species is morphologically most related to Casearia souzae R.Marquete & Mansano, being distinguished by its leaf, sepals and ovary without glands, leaf apex with no apicule, internal surface of the sepals glabrous, lobes of the nectariferous disc oblong and densely pilose, and stigma glabrous.